A framework for sustainable supply chains: evaluation of implementation barriers. (2018) - Bahinipati, Bikram K.; Panigrahi, Swayam Sampurna
Sustainable supply chain management (SSCM) identifies and integrates a set of key business processes to provide products, services and information for value addition through collaborative and sustainable efforts of supply chain members. In order to accomplish this objective, sustainable supply chain practices need to be implemented to ensure a strong and healthy society without compromising the performance limits and governance, while attaining the environmental, economic, and social goals. The literature and industry experts have identified the critical inhibiting indicators for the successful implementation of SSCM practices. The sustainable supply chain evaluates different alternatives against multiple sustainable practice attributes which should be considered simultaneously to arrive at an appropriate implementation decision. The focus of this paper is to develop a framework for implementation of sustainable practices in Indian small and medium enterprises (SMEs) for competitive advantage. An analytic hierarchy process (AHP) framework has been proposed for SMEs to resolve the conflicts and quantify the impact of critical inhibitors on SSCM implementation. The assessment of the priority weight of these inhibitors would help the decision makers to prioritise the action plan for implementation of SSCM practices. A sensitivity analysis is conducted to identify the sensitive points in the decision process.